Menakar Permasalahan Pendidikan Islam dalam Presfektif Islam Transitif - Rustam Ependi (Sekolah Tinggi Agama Islam Sumatera Medan, 2020)
Educational problems in the modern era are not only limited to systems, methods and strategies, but rather how to prepare future generations. The phenomenon in the modern era shows that the younger generation grows with an individualistic and pragmatic attitude. So that many graduates of educational institutions are trapped in understanding their teachings more deeply, so that the virtue of Islam, which is actually very broad, becomes stagnant and narrow because it is only for oneself. The Transitive Islamic perspective requires that the output of the graduates of Islamic education institutions be agents of change or be transitive. In the sense of an outward movement, which is not only selfish but also tries to make other people get safety, security, peace, prosperity and even the happiness of life in this world and the hereafter.